Estudo da viscosidade aparente em sistemas óleo e água visando o escoamento em oleodutos - Pessoa, João Henrique Brito (2014)
The oil production over time and degree of exploitation of the reservoirs, carries an increasing flow of formation water. This produced water tends to form emulsions with oil both within the reservoir as in the ducts that drain the production. The stabilized emulsion formed by the oil itself components ( asphaltenes , resins, lubricants , etc.) tends to cause an increase in fluid viscosity effect , and consequently , an increase in pressure loss in pipes . The measurement of the viscosity of these emulsified fluids in flow conditions is a complex problem, because the flow patterns formed in the pipes differ from the configuration in which the fluid is introduced in a viscometer. In addition to all the uncertainty in terms of obtaining the characteristics of the flowing fluids the industrial flow systems presents itself under a complex network with several pumping stations along the transfer ducts and mixing oils of different characteristics. Given this, it was developed a loop test in laboratorial scale for emulsions of water and oil in order to determine, under a controlled manner, the apparent viscosity of the emulsions varying parameters such as water content and total flow rate. A large set of data were collected from a real system flow and , through a statistical analysis of these data and the use of equations for the flow in pipes, was obtained the apparent viscosity curve as a function of water content . Finally, viscosity data were obtained from a series of emulsions as a function of the water content using a Brookfield rheometer. All these data were analyzed in order to determine the best method to obtain the apparent viscosity of the working fluid and thereby obtain a better description of the flow.